A new bibenzyl and 9, 10-dihydrophenanthrene derivative from aerial parts of crowberry (Empetrum nigrum L.). (April 2021) - Ponkratova, Anastasiia O.; Whaley, Andrei K.; Balabas, Olga A.; Smirnov, Sergey N.; Proksch, Peter; Luzhanin, Vladimir G.
Graphical abstract: Highlights: A new methoxylated bibenzyl and 9, 10-phenanthrene were isolated from the shoots of Empetrum nigrum . Structures of the isolated compounds were elucidated by spectroscopic methods. The first time 1-(3-hydroxyphenyl)-2-(3-hydroxy-4, 5-dimethoxyphenyl)ethane was shown to be contained in E. nigrum . Abstract: Two new natural products - 1 and 2, together with four known compounds (3-6 ) were isolated from aerial parts of crowberry ( Empetrum nigrum L.). All structures were elucidated by extensive 1D and 2D NMR experiments and HR-ESIMS data along with comparison of their spectroscopic data with those reported in the literature. Compound 1 (1-(3, 5-dihydroxy-4-methoxyphenyl)-2-phenylethane) is a bibenzyl (dihydrostilbene) derivative. Compound 2 was found to be 6-hydroxy-2, 3, 4-trimethoxy-9, 10-dihydrophenantrene. Compounds 3 and 4 were established as 4, 7-dihydroxy-2, 3-dimethoxy-9, 10-dihydrophenantrene (ephemeranthol-A) and 1-(3-hydroxyphenyl)-2-(3-hydroxy-4, 5-dimethoxyphenyl)ethane, respectively. Compounds 5 and 6 were identified as 4′-hydroxy-2′-methoxydihydrochalcone and 2′, 4′-dihydroxychalcone, respectively.